A Study on Disease Patterns and Treatment Seeking Behaviors among the University Resident Students (Bangladesh Pharmaceutical Journal, 2020)
As one of the fundamental human rights, healthcare is usually sought during illness episode. A questionnaire-based survey was conducted on 221 residential university students to identify the existing disease patterns and treatment seeking behaviors. Among the students, 22.17% were devoid of normal body-weight and 45.7% of them exercise at least three days a week. Based on smoking habits they were non-smoker (60.18%), smoker (25.34%), and second-hand smoker (14.48%). Besides, 33.03% of them have an allergy (seasonal: 24.43%; perennial: 8.60%) and 75.11% of students’ family members have or had at least one of the eight specified diseases. In 2019, around 98% of the students had suffered from at least one illness like fever-all types (86.43%), common cold (52.94%), diarrhea (20.36%), cough (46.61%), nasal congestion (10.86%), pain/aches-all types (25.79%), gastric problems (49.32%), skin diseases (15.38%), dental diseases (1.36%), eye diseases (0.9%), and many other diseases (4.52%). To mitigate these illnesses majority took medications instead of self-recovery that was highest for dental and eye diseases (100%), and lowest for cough (58.25%) and nasal congestion (58.33%). Usually, 61.99% of the residents go to Government Hospital (DMCH: 45.70%, BSMMU: 9.95%) for seeking treatment followed by University Medical Center (41.63%), Private Medical Consultant (5.88%), Private Hospital (4.52%), and others (3.62%). Moreover, 67.42% of the students take prescribed medicines as stated in prescriptions. As there is a tendency among 83.26% of the students to take medicines without prescriptions, raising awareness on the detrimental impacts of self-treatment is needed to refrain them from self-medication practices.Bangladesh Pharmaceutical Journal 23(2): 187-194, 2020